Do agricultural services contribute to grain production? The heterogeneity analysis based on service categories and service sources - Zhu, Weijing; Sun, Xiaoyu; Qi, Zhenhui (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgricultural services have a substitution effect on agricultural labor. But few studies have considered the impact of agricultural services on grain production from the perspective of heterogeneity in services categories and sources. Therefore, this study examines the impact of agricultural services on grain production in China and explores its heterogeneous effects.MethodsUtilizing data from the 2018 China Labor-force Dynamics Survey (CLDS2018), this study examines the impact of agricultural services on grain production through the PSM method. Secondly, robustness and endogeneity checks were conducted using IPWRA and IV-probit models, respectively. Finally, heterogeneity analysis was conducted on service categories and sources.ResultsAgricultural services can contribute to grain production; the robustness and endogeneity tests also confirmed this finding. However, there are heterogeneous effects in the service categories and service sources. In detail, machinery service and technical service have positive effect on grain production except agricultural materials supply service. And the positive effect of agricultural services was significant when the supplier of the services is government or voluntary organizations.DiscussionBased on the above findings, promoting the development of service markets and establishing a favorable market environment will enhance the positive impact of agricultural services on grain production, thereby contributing to ensure food security in developing countries with millions of small households.